Longitudinal preclinical magnetic resonance imaging of diffuse tumor burden in intramedullary myeloma following bortezomib therapy. (17th June 2019) - Hathi, Deep K.; Engelbach, John A.; Hillengass, Jens; Veis, Deborah; Achilefu, Samuel; Garbow, Joel R.; Shokeen, Monica
Abstract : Multiple myeloma (MM) is a largely incurable, debilitating hematologic malignancy of terminally differentiated plasma cells in the bone marrow (BM). Identification of therapeutic response is critical for improving outcomes and minimizing costs and off‐target toxicities. To assess changes in BM environmental factors and therapy efficacy, there is a need for noninvasive, nonionizing, longitudinal, preclinical methods. Here, we demonstrate the feasibility of preclinical magnetic resonance imaging (MRI) for longitudinal imaging of diffuse tumor burden in a syngeneic, immunocompetent model of intramedullary MM. C57Bl/KaLwRij mice were implanted intravenously with 5TGM1‐GFP tumors and treated with a proteasome inhibitor, bortezomib, or vehicle control. MRI was performed weekly with a Helmholtz radiofrequency coil placed on the hind leg. Mean normalized T1‐weighted signal intensities and T2 relaxation times were quantified for each animal following manual delineation of BM regions in the femur and tibia. Finally, tumor burden was quantified for each tissue using hematoxylin and eosin staining. Changes in T2 relaxation times correlated strongly to cell density and overall tumor burden in the BM. Median T2 relaxation times and regional T1‐weighted contrast uptake were shown to be most relevant in identifying posttherapy disease stage in this model of intramedullary MM. In summary, our results highlighted potential preclinical MRI markers for assessing tumor burden and BM heterogeneity following bortezomib therapy, and demonstrated the application of longitudinal imaging with preclinical MRI in an immunocompetent, intramedullary setting. Abstract : There is a scarcity of preclinical MRI studies of bone marrow malignancies. Here, we demonstrate longitudinal MRI of the bone marrow in response to multiple myeloma stage and therapy in an immunocompetent, intramedullary model. The key findings were that T1‐weighted contrast‐enhanced signal and T2 relaxation times are indicative of spatiotemporal disease progression and response to proteasome inhibitor therapy. Histology of the bone marrow validated the MR observations.